Two arm single-blind parallel randomized controlled trial effects of health education intervention on foot self-care behavior among diabetic patients: study protocol - Oluchi, Sampson Emilia; Abdul Manaf, Rosliza; Ismail, Suriani; Kadir Shahar, Hayati; Udeani, Theophilus Kachidelu; Uchegbu, Uchenna Nwachinemere (Universiti Putra Malaysia Press, 2023)
Introduction: Diabetes is a chronic illness and it has a significant impact on health. Behavioral interventions theory could improve self-care practices of the foot among patients with diabetic. Behavioral interventions could prevent the risk of foot problems. This trial aims at determining the effect of patient education intervention on foot self-care behavior and clinical outcomes among diabetes patients. Methods: The study is a two-arm single-blinded randomized controlled trial which will be conducted in the Federal Medical Centre (FMC) Owerri, Imo state, Nigeria involving 160 diabetic patients. A central computer-generated randomization list will be generated. Sequentially numbered sealed opaque envelopes will be used to determine concealment. The sample size is 160; therefore 80 participants will receive three sessions of patient education in addition to usual care (intervention group) for three and six months while another 80 participants (control group) will receive only usual care and will receive health education after the study is completed. The outcome of the intervention effectiveness is measured by modified version of Diabetes foot Self-Care Behavior Scale (DFSBS). Discussion: Our hypothesis is that based on the Health Belief Model, patient education intervention can improve foot self-care behavior in the intervention group. Data collection will be done at baseline, and at three- and six-months post intervention.